2015
DOI: 10.1038/srep12052
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-methylated 3-hydroxypyridines hinder hen egg-white lysozyme fibrillogenesis

Abstract: Protein aggregation with the concomitant formation of amyloid fibrils is related to several neurodegenerative diseases, but also to non-neuropathic amyloidogenic diseases and non-neurophatic systemic amyloidosis. Lysozyme is the protein involved in the latter, and it is widely used as a model system to study the mechanisms underlying fibril formation and its inhibition. Several phenolic compounds have been reported as inhibitors of fibril formation. However, the anti-aggregating capacity of other heteroaromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…As shown in Fig. 1b , the aggregation kinetics of HEWL exhibit a typical sigmoidal appearance containing a lag phase associated with nucleation, a fast growth phase linked to the elongation and propagation of fibrils, and a final stationary phase 28 . Further, these results are in agreement with the nucleation dependent polymerisation for amyloidogenic proteins.…”
Section: Resultsmentioning
confidence: 91%
“…As shown in Fig. 1b , the aggregation kinetics of HEWL exhibit a typical sigmoidal appearance containing a lag phase associated with nucleation, a fast growth phase linked to the elongation and propagation of fibrils, and a final stationary phase 28 . Further, these results are in agreement with the nucleation dependent polymerisation for amyloidogenic proteins.…”
Section: Resultsmentioning
confidence: 91%
“…Aliquots of the samples without or with taxifolin were withdrawn at 0 and 7 days of incubation and subjected to SDS-PAGE. As shown in Fig 4 , the protein incubated alone displayed both high molecular weight assemblies (corresponding to amyloid fibrils) trapped in the well of the stacking gel and a range of low-molecular weight bands corresponding to acid-induced hydrolysis of the monomeric structure[ 46 , 47 ]. A similar pattern was observed for samples containing 25 and 50 μM taxifolin, indicating that the polyphenol did not protect the protein against acidic proteolysis at these concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports demonstrating that polyphenols are effective inhibitors of protein fibrillation [ 12 , 13 , 17 20 ], through interaction with one or more of the amyloidogenic species, produced during the course of the aggregation process. For instance, some polyphenols prevent amyloid formation by interacting with and stabilizing native structure of proteins [ 47 , 58 , 61 ]; while others bind to prefibrillar structures and redirect amyloidogenic polypeptides into unstructured, off-pathways oligomers [ 62 ], or toward an alternative non-toxic disordered (amorphous) aggregation pathway [ 20 ]. Recently, Hirohata et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the objective of this study was to investigate the effect of high temperatures on the formation of amyloid fibrils using the protein model of HEWL. Previous studies have demonstrated that HEWL protein could form into amyloid fibrils at 54°C in 50 mM glycine of pH 2.2 (Seraj et al., 2019), 60°C in NaCl and KCl solution of pH 2.0 (Marino et al., 2015), and 65°C in 500 mM glycine of pH 2.0 (Sivalingam et al., 2016). All these previously reported higher temperatures used to generate HEWL amyloid fibrils are specific.…”
Section: Introductionmentioning
confidence: 99%